Multidrug resistance patterns and carbapenemase production among Gram-negative bacteria causing healthcare-associated infections in hospitalized patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Kindu Alem; Mucheye Gizachew; Mulat Dagnew; Worku Ferede; Solomon Belay; Baye Gelaw; Feleke Moges (PLoS ONE, 2026)
Background Klebsiella pneumoniae , Acinetobacter species, and Pseudomonas aeruginosa are priority pathogens identified by the World Health Organization that have emerged as major causes of healthcare-associated infections. Their increasing resistance to multiple antimicrobial agents poses significant challenges to clinical management and infection control efforts. Objective This study aimed to determine the prevalence, associated risk factors, antimicrobial resistance patterns, and carbapenemase production of K. pneumoniae , Acinetobacter spp., and P. aeruginosa among hospitalized patients with suspected bloodstream, urinary tract, and surgical site healthcare-associated infections at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Methods A hospital-based cross-sectional study was conducted from August 2024 to June 2025 among 477 patients suspected of bloodstream, urinary tract, or surgical site healthcare-associated infections. Socio-demographic and clinical data were collected using a semi-structured questionnaire. Blood, urine, and wound/pus specimens were aseptically collected and inoculated on MacConkey, blood, and cysteine lactose electrolyte-deficient agar following standard microbiological techniques. Antimicrobial susceptibility testing was performed using the Kirby-Bauer disc diffusion method on Mueller-Hinton agar according to Clinical and Laboratory Standards Institute guidelines. Data were analyzed using SPSS version 27. Bivariate and multivariate logistic regression analyzes were used to identify factors associated with healthcare-associated infections. P value < 0.05 was considered statistically significant. Results Among the 477 patients, 118 (24.7%) developed healthcare-associated infections caused by K. pneumoniae , Acinetobacter spp., and P. aeruginosa , with culture positivity rates of 14.9%, 4.8%, and 5%, respectively. Significant associated factors included age under five (AOR = 13.260, p < 0.001) and 5–17 (AOR = 4.081, p < 0.025), prior hospital admission (AOR = 8.302, p < 0.001), prolonged hospital stay (AOR = 3.213, p < 0.001), and admission to the orthopedic ward (AOR = 6.071, p < 0.003). Multidrug resistance was detected in 94.4% of K. pneumonia e, 69.6% of Acinetobacter spp., and 58.3% of P. aeruginosa isolates. Carbapenemase production occurred in 92%, 77.8%, and 57.1% of these carbapenem-resistant isolates, respectively. Amikacin, meropenem, and ciprofloxacin were the most effective antimicrobials, whereas chloramphenicol was effective only against K. pneumonia e. Conclusion This study showed high prevalence of multidrug resistance and carbapenemase production among K. pneumoniae , Acinetobacter spp., and P. aeruginosa in the study area, highlighting the urgent need to strengthen infection prevention and control measures and to promote antimicrobial stewardship programs.